Identification of Candidate Genes Potentially Relevant to Chamber-Specific Remodeling in Postnatal Ventricular Myocardium. (24th March 2010) - Torrado, Mario; Iglesias, Raquel; Nespereira, Beatriz; Mikhailov, Alexander T.
Abstract : Molecular predisposition of postnatal ventricular myocardium to chamber-dependent (concentric or eccentric) remodeling remains largely elusive. To this end, we compared gene expression in the left (LV) versus right ventricle (RV) in newborn piglets, using a differential display reverse transcription-PCR (DDRT-PCR) technique. Out of more than 5600 DDRT-PCR bands, a total of 153 bands were identified as being differentially displayed. Of these, 96 bands were enriched in the LV, whereas the remaining 57 bands were predominant in the RV. The transcripts, displaying over twofold LV-RV expression differences, were sequenced and identified by BLAST comparison to known mRNA sequences. Among the genes, whose expression was not previously recognized as being chamber-dependent, we identified a small cohort of key regulators of muscle cell growth/proliferation (MAP3K7IP2, MSTN, PHB2, APOBEC3F) and gene expression (PTPLAD1, JMJD1C, CEP290), which may be relevant to the chamber-dependent predisposition of ventricular myocardium to respond differentially to pressure (LV) and volume (RV) overloads after birth. In addition, our data demonstrate chamber-dependent alterations in expression of as yet uncharacterized novel genes, which may also be suitable candidates for association studies in animal models of LV/RV hypertrophy.